YebC, a putative transcriptional factor involved in the regulation of the proteolytic system of Lactobacillus - Brown, Lucia (2017)
The proteolytic system of Lactobacillus plays an essential role in bacterial growth, contributes to the flavor development of fermented products, and can release bioactive health-beneficial peptides during milk fermentation. In this work, a genomic analysis of all genes involved in the proteolytic system of L. delbrueckii subsp. lactis CRL 581 was performed. Genes encoding the cell envelope-associated proteinase, two peptide transport systems, and sixteen peptidases were identified. The influence of the peptide supply on the transcription of 23 genes involved in the proteolytic system of L. delbrueckii subsp. lactis was examined after cell growth in a chemically defined medium (CDM) and CDM supplemented with Casitone. prtL, oppA 1, optS, optA genes as well as oppDFBC and optBCDF operons were the most highly expressed genes in CDM; their expression being repressed 6- to 115-fold by the addition of peptides. The transcriptional analysis was confirmed by proteomics; the up-regulation of the PrtL, PepG, OppD and OptF proteins in the absence of peptides was observed while the DNA-binding protein YebC was up-regulated by peptides. Binding of YebC to the promoter region of prtL, oppA 1, and optS, demonstrated by electrophoretic mobility shift assays, showed that YebC acts as a transcriptional repressor of key proteolytic genes.